Identifying the Mental Model of the Managers of Melli Bank Regarding Quantum Leadership using Q-methodology - Shariatikia, Ghasem; Beheshtifar, Malikeh; Montazeri, Mohammad; Kazemi, Hossein (Cuestiones Políticas, 2020)
At Bank Melli Iran, which is the site of research, there are different opinions and views on quantum leadership, each of which is representing a specific intellectual model on the subject. These diverse opinions form a space for discourse. This study will identify this discursive space in detail and also analyze it in order to reveal organizational models to present strategies to plan the improvement of Bank Melli’s policies and plans. The methodology used in this research is Q-sort or Q-methodology. This methodology was able to reveal several courses in the speech forum. Studying discursive space, 74 factors were detected. In analyzing these propositions, finally, 59 factors formalized Q expressions. These propositions that form the Q order, were written by paras on 59 cards. A sample of Bank Melli managers was then selected using Q-sort arrange for these cards on the Q-chart using defined instructions. In interpreting and the results obtained, three large models were identified including the ambassadors of change, the pioneers of protection and the drivers of stability.